2008
DOI: 10.3923/pjbs.2008.490.492
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Hyper Accumulator Plants in Copper and Iron Mine in Iran

Abstract: The aim of present study was to identify accumulator plants that are effective for phytoremediation. We chose a mine of Iron and Copper named Hame Kasi that located western north of Hamedan city as a polluted area. In this region concentration of heavy metals is several times more than non-polluted area. Seventeen plant species and 6 soil samples were collected from this region for determination of heavy metals content. Atomic Absorption Spectrophotometer (AAS) was used for analysis of heavy metals in soil and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 3 publications
1
27
0
2
Order By: Relevance
“…As shown in Table 1, the amounts of Fe, Mn, Zn, and Cu were, respectively, 17, 12, 12.5, and 11.2 times higher than those in the nonpolluted soils [11]. C. botrys L. was collected from January to June in 2007.…”
Section: Sampling Area Characterizationmentioning
confidence: 99%
“…As shown in Table 1, the amounts of Fe, Mn, Zn, and Cu were, respectively, 17, 12, 12.5, and 11.2 times higher than those in the nonpolluted soils [11]. C. botrys L. was collected from January to June in 2007.…”
Section: Sampling Area Characterizationmentioning
confidence: 99%
“…Heavy metals in soil and plant samples, tested plant species were grouped on the basis of their accumulation capability of heavy metals. The results of this research showed that there are some hyper accumulator plants in this area that can concentrate heavy metals in their different parts thus they can be used for remediation of polluted area (Behrouz E. Malayeri, 2008).Treatment methods were developed to reduce the hazardous elements in wastewater before its use on agricultural fields. However, in many developing countries wastewater is still used without any treatment as treatment facilities are not available, people are not aware of the health and environmental hazards and the WHO guidelines are not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…It is documented that, heavy metals cause oxidative stress (Mudipalli 2008 ) by formation of free radicals. Furthermore, they can replace essential metals in pigments or enzymes disrupting their function (Malayeri et al 2008 ). Regarding their toxicities, the most problematic heavy metals are As, Cd, Cr, Cu, Hg, Pb, Se, Sn, and Zn (Ghosh 2010 ).…”
Section: Usepa ( 2000 )mentioning
confidence: 99%